ANALISIS IMPLEMENTASI STRATEGI PEMASARAN PARIWISATA DAERAH PADA DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA KABUPATEN KULON PROGO, DAERAH ISTIMEWA YOGYAKARTA - NOOR, RISWAN M. ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The purpose of this study is to get a response from problems the researcher questions, namely: (1) to deskrepsi internal factors (product, price, promotion, place / distribution) that affect the level of tourists visiting Kulon Progo